Efektivitas Penggunaan Media Interaktif Powerpoint Terhadap Hasil Belajar PAI di SD Angkasa II Lanud Padang - Tiyan, Ratih Nindea; Satria, Rengga (Universitas Negeri Padang, 2024)
Recently, the world of education has experienced complex problems, a lack of understanding of Islamic Religious Education material, so that student learning outcomes have not been able to meet the standard criteria for achieving learning objectives. This is proven that only 14.28% of students were able to achieve the KKTP before using interactive powerpoint media, whereas in class V it was only 23.52%. Therefore, it is necessary to provide interactive powerpoint media. This media is considered practical, allows for an active response from the recipient of the message and is healthier than a whiteboard. The aim of the research is to analyze the effectiveness of using PowerPoint interactive media on the learning outcomes of Islamic religious education for students at Angkasa II Lanud Padang Elementary School. The method used in this research was pre-experiment with a one group pretest posttest design. The research results show that the calculated t value is greater than the t table, namely 7,170 > 2,179 for class IV and 25,606 > 2,131 for class V, meaning that the use of interactive powerpoint media is effective in improving learning outcomes.